Legitimasi Masyarakat Internasional Terhadap Intervensi Kemanusiaan Dewan Keamanan Perserikatan Bangsa-Bangsa (PBB) Tahun 2011 - Darnela, Lindra (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Massive demonstrations that occurred since 2010 in several Arab countries (Arab Spring) sparked the attention of the UN Security Council to undertake humanitarian intervention, including in Libya which started in February 2011 with the use of armed force undertaken by NATO and some other big countries. Humanitarian intervention is a recommendation of the UN Security Council Resolution 1973 of 2011, under Chapter VII of the UN Charter, 1945. In doing humanitarian intervention, state and international organizations must have the recommendation of the UN Security Council, but the Security Council should also get legitimacy from the international community. Humanitarian intervention is also required to have humanitarian objectives to protect human rights. In this paper discusses the legitimacy given by the international community to the humanitarian intervention of the UN Security Council on Libya.